2021
DOI: 10.1039/d0fo02448a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of DHA and EPA in high fat-induced insulin resistant mice

Abstract: Docosahexaenoic acid (DHA, 22:6) and eicosapentaenoic acid (EPA, 20:5) exert their anti-obesity effect by mechanisms dependent or independent of PPARγ and GPR120 signaling in insulin resistant mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
4
19
0
Order By: Relevance
“…Solid particles could be irreversibly adsorbed at the oil-water interface to form stable Pickering emulsions. Pickering emulsions are generally considered highly stable because the interfacial adsorption of the particle stabilizers is almost irreversible [ 52 , 53 ]. The solid particles could be irreversibly adsorbed to the oil-water interface as a physical barrier, which could provide high stability for DHA and reduce the oxidation of DHA.…”
Section: Delivery Systems Of Dhamentioning
confidence: 99%
“…Solid particles could be irreversibly adsorbed at the oil-water interface to form stable Pickering emulsions. Pickering emulsions are generally considered highly stable because the interfacial adsorption of the particle stabilizers is almost irreversible [ 52 , 53 ]. The solid particles could be irreversibly adsorbed to the oil-water interface as a physical barrier, which could provide high stability for DHA and reduce the oxidation of DHA.…”
Section: Delivery Systems Of Dhamentioning
confidence: 99%
“…These include upregulation of peroxisome proliferator-activated nuclear receptor-γ (PPARγ), prevention of macrophage infiltration, activation of NF-κB and Jun N-terminal Kinase (JNK) signaling pathways, suppression of leukocyte chemotaxis and blocking of pro-inflammatory cytokines and eicosanoid production. 17–19 Furthermore, data from mice fed a high-fat diet showed that DHA could downregulate G Protein-Coupled Receptor 120 (GPR120) and stimulate the browning of white adipose tissue. 17,20,21 Although there are some potentially beneficial biological effects of DHA, the molecular mechanism by which DHA exerts its nutritional effects in the liver was not detected in fish.…”
Section: Introductionmentioning
confidence: 99%
“…17–19 Furthermore, data from mice fed a high-fat diet showed that DHA could downregulate G Protein-Coupled Receptor 120 (GPR120) and stimulate the browning of white adipose tissue. 17,20,21 Although there are some potentially beneficial biological effects of DHA, the molecular mechanism by which DHA exerts its nutritional effects in the liver was not detected in fish.…”
Section: Introductionmentioning
confidence: 99%
“…However, DHA shows anti-in ammatory effects in several ways under different conditions. These include up-regulation of peroxisome proliferatoractivated nuclear receptor-γ (PPARγ), prevention of macrophage in ltration, activation of NF-κB and Jun N-terminal Kinase (JNK) signaling pathways, suppression of leukocyte chemotaxis and blocking of proin ammatory cytokine and eicosanoid production [17][18][19]. Furthermore, data from mice fed a high-fat diet showed that DHA could down-regulate G Protein-Coupled Receptor 120 (GPR120) and stimulate the browning of white adipose tissue [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…These include up-regulation of peroxisome proliferatoractivated nuclear receptor-γ (PPARγ), prevention of macrophage in ltration, activation of NF-κB and Jun N-terminal Kinase (JNK) signaling pathways, suppression of leukocyte chemotaxis and blocking of proin ammatory cytokine and eicosanoid production [17][18][19]. Furthermore, data from mice fed a high-fat diet showed that DHA could down-regulate G Protein-Coupled Receptor 120 (GPR120) and stimulate the browning of white adipose tissue [17,20,21]. Although there are some potentially bene cial biological effects of DHA, the molecular mechanism by which DHA exerts its nutritional effects in the liver was not detected in sh.…”
Section: Introductionmentioning
confidence: 99%